2007
DOI: 10.1007/s00428-007-0515-3
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and ultrastructural evidence of endoplasmic reticulum stress in LGMD2I

Abstract: Limb girdle muscular dystrophy type 2I (LGMD2I) is due to mutations in the fukutin-related protein gene (FKRP), encoding a putative glycosyltransferase involved in alpha-dystroglycan processing. To further characterize the molecular pathogenesis of LGMD2I, we conducted a histological, immunohistochemical, ultrastructural and molecular analysis of ten muscle biopsies from patients with molecularly diagnosed LGMD2I. Hypoglycosylation of alpha-dystroglycan was observed in all FKRP-mutated patients. Muscle histopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…The studies include few patients and have employed different methods for clinical and histopathological assessment. However, five homozygous patients studied by Boito et al [21] showed an apparent correlation between the clinical grading and pathology severity score, with an inverse correlation to age of onset. In contrast, four homozygous patients studied by Yamamoto et al [12] all showed a mild clinical course with no obvious correlation with age of onset and histopathological alterations.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The studies include few patients and have employed different methods for clinical and histopathological assessment. However, five homozygous patients studied by Boito et al [21] showed an apparent correlation between the clinical grading and pathology severity score, with an inverse correlation to age of onset. In contrast, four homozygous patients studied by Yamamoto et al [12] all showed a mild clinical course with no obvious correlation with age of onset and histopathological alterations.…”
Section: Discussionmentioning
confidence: 92%
“…However, Jimenez-Mallebrera et al [13] found some inconstancies between levels of α-DG glycosylation determined by IHC and the clinical course in patients harbouring mutations in fukutin and FKRP. Furthermore, Boito et al [21] found variable reduction of glycosylated α-DG in patients investigated by IHC and, interestingly, by immunoblot analysis they detected only trace amounts of glycosylated α-DG in three c.826C>A homozygotes of whom one was asymptomatic [4]. The result presented in this work demonstrates a huge variability in the levels of glycosylated α-DG among the homozygous patients, however, we observed no systematic correlation between the level of α-DG glycosylation and walking function or histopathological alterations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up-regulation of BiP/GRP78 was reported in muscle biopsies from LGMD2I patients (67). To verify this result, we have studied muscle biopsies from patients with a number of molecularly characterized dystroglycanopathies.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought to physically interact with POMGnT1 and regulate its activity. Its deficiency in tis sue seems to elicit the unfolded protein response (UPR) [91] . Further, POMGnT1 is co-precipitated with FKTN and mice with knockin mutations in FKTN have a decreased POMGnT1 activity [90] .…”
Section: Congenital Muscular Dystrophiesmentioning
confidence: 99%